Exploring Local Wisdom via Community-Based Tourism for Sustainable Tourism Development in Cigugur, Kuningan, Indonesia - ., Darto; Aditiany, Savitri; Myrna, Rita; Kamila, Nabila (Journal of Ecohumanism, 2025)
Tourism plays a crucial role in Indonesia's economy, contributing significantly to income generation, employment, and the preservation of cultural heritage. Community-Based Tourism (CBT) is an effective model that involves local communities in managing tourism, ensuring that its economic benefits are directly experienced by residents. Local wisdom, which refers to traditional knowledge passed down through generations, is vital for fostering sustainable tourism by offering unique cultural and natural attractions. The Cigugur Subdistrict in Kuningan Regency Indonesia, rich in cultural and natural resources, faces challenges in fully optimizing its tourism potential. This study examines the role of local wisdom in tourism development through CBT in Cigugur Village. Qualitative research methods, including observations, interviews, and literature reviews, were used to investigate how local wisdom can be incorporated into CBT to promote inclusive tourism development. The results emphasize the importance of community participation, sustainable management practices, and collaborative partnerships to ensure the success of tourism in Cigugur. This approach can serve as a model for achieving a balance between cultural preservation and economic growth through community-based tourism.